Cultured meat and challenges ahead: A review on nutritional, technofunctional and sensorial properties, safety and legislation - Keshia Broucke; Els Van Pamel; Els Van Coillie; Lieve Herman; Geert Van Royen (Meat Science, 2023)

Longitudinal screening of antibiotic residues, antibiotic resistance genes and zoonotic bacteria in soils fertilized with pig manure - Tina Van den Meersche; Geertrui Rasschaert; Thijs Vanden Nest; Freddy Haesebrouck; Lieve Herman; Els Van Coillie; Stephanie Van Weyenberg; Els Daeseleire; Marc Heyndrickx (Environmental Science and Pollution Research, 2020)

EFSA’s scientific activities and achievements on the risk assessment of genetically modified organisms (GMOs) during its first decade of existence: looking back and ahead - Yann Devos; Jaime Aguilera; Zoltán Diveki; Ana Gomes; Yi Liu; Claudia Paoletti; Patrick du Jardin; Lieve Herman; Joe N. Perry; Elisabeth Waigmann (Transgenic Research, 2014)

Molecular Detection and Genotyping of Noroviruses - Ambroos Stals; Elisabeth Mathijs; Leen Baert; Nadine Botteldoorn; Sarah Denayer; Axel Mauroy; Alexandra Scipioni; Georges Daube; Katelijne Dierick; Lieve Herman; Els Van Coillie; Etienne Thiry; et al. (Food and Environmental Virology, 2012)

A Review of Known and Hypothetical Transmission Routes for Noroviruses - Elisabeth Mathijs; Ambroos Stals; Leen Baert; Nadine Botteldoorn; Sarah Denayer; Axel Mauroy; Alexandra Scipioni; Georges Daube; Katelijne Dierick; Lieve Herman; Els Van Coillie; Mieke Uyttendaele; et al. (Food and Environmental Virology, 2012)

Mycotoxin production by pure fungal isolates analysed by means of an uhplc-ms/ms multi-mycotoxin method with possible pitfalls and solutions for patulin-producing isolates - Els Van Pamel; Geertrui Vlaemynck; Marc Heyndrickx; Lieve Herman; Annemieke Verbeken; Els Daeseleire (Mycotoxin Research, 2011)

Seasonal influence on heat‐resistant proteolytic capacity of Pseudomonas lundensis and Pseudomonas fragi , predominant milk spoilers isolated from Belgian raw milk samples - Sophie Marchand; Kim Heylen; Winy Messens; Katleen Coudijzer; Paul De Vos; Koen Dewettinck; Lieve Herman; Jan De Block; Marc Heyndrickx (Environmental Microbiology, 2009)
Summary Psychrotolerant bacteria and their heat‐resistant proteases play a major role in the spoilage of UHT‐processed dairy products. Summer and winter raw milk samples were screened for the presence of such bacteria. One hundred and three proteolytic psychrotolerant bacteria were isolated, characterized by API tests, rep‐PCR fingerprint analysis and evaluated for heat‐resistant protease production. Twenty‐nine strains (representing 79% of the complete collection) were further identified by 16S rRNA gene sequencing, rpoB gene sequencing and DNA–DNA hybridizations. A seasonal inter‐ and intra‐species influence on milk spoilage capacity (e.g. growth rate and/or protease production) was demonstrated. Moreover, this polyphasic approach led to the identification of Pseudomonas fragi and Pseudomonas lundensis (representing 53% of all isolates) as predominant producers of heat‐resistant proteases in raw milk. The role of Pseudomonas fluorescens , historically reported as important milk spoiler, could not unequivocally be established. The use of more reliable identification techniques and further revision of the taxonomy of P. fluorescens will probably result in a different perspective on its role in the milk spoilage issue.